Relationships between the P status of surface and deep horizons of agricultural soils under various cropping systems and for different soil types: a case study in Belgium. (5th March 2013) - Renneson, M.; Dufey, J.; Legrain, X.; Genot, V.; Bock, L.; Colinet, G.
Abstract: Application of phosphorus (P) fertilizers to agricultural soils should be based on sound knowledge about soil P reserves, availability and lability to optimize conditions for plant uptake while limiting P transport to surface waters. This study investigated relationships between parent material (PM), land use and P fractions in agricultural soils at a regional scale. Surface and deep (100–120 cm) soil samples were collected from 120 agricultural sites (240 total samples) and analysed for three P forms (inorganic, organic and available) as well as for additional key properties. Land uses within the study area were continuous cropland, permanent pasture and temporary grassland. The area covered the 12 most common parent types in Wallonia. Mean total P contents were 904 and 401 mg/kg in surface and deep samples, respectively, with a 33% coefficient of variation for both horizons. The organic P fraction represented, on average, 30% of total P, while available P corresponded to 9% of total P. The influence of PM was apparent in both the surface and deep soil samples, while land use influenced only surface properties. The pattern in total P content relative to land use was pasture ≥ cropland ≥ temporary grassland. Correlation analyses highlighted significant relationships between edaphic parameters viz Alox, Feox, CEC, TOC, pH and P content, the main soil parameter being Alox which determines P sorption capacity. An enrichment factor was used to distinguish between geogenic sources and human activities in terms of topsoil P content.